Analysis of Caring Economics in Society at Samarinda - Lutfi Saidatus Saniah; Reza, Reza; Permatasari, Indah (Educational Studies: Conference Series, 2023)
A caring attitude makes people able to help each other. If a caring attitude is used properly, humans will become more respectful to each other. Caring economics gives rise to a new outlook on economics that can build good qualities such as generosity, honesty, cooperation and mutual help. The aim of this research is to determine caring economics in the community in Samarinda. The subjects of this research are people who trade in the ijabah market and kedondong market. This type of research uses descriptive with a qualitative approach. The data collection techniques used were observation and interviews. The data analysis techniques used include data reduction, data presentation and conclusions/verification. The research results show that traders in the Ijabah market and Kedondong market have implemented a caring economic attitude such as having a rational attitude in trading, being honest, generous, and contributing to each other with fellow traders out of a sense of humanity.